Representation of Gendered Language in English Textbook for Indonesian Junior High Schools - Ni Komang Arie Suwastini; Putu Wiraningsih; Kadek Eva Krishna Adnyani (International Journal of Language Education, 2023)
As gender constructs could be disseminated through language, English textbooks could be a fertile arena to maintain or deconstruct traditional gender constructs.  Since seventh grade students are in their stage to assert their sexual identity, their exposure to English textbook could affect their perception of gendered positions in the society. The present study purposefully aimed to analyzed the language used in English textbook for Grade 7, because the book was published by the Indonesian Ministry of National Education and recommended to be used nationally in public schools in Indonesia. Designed as a descriptive qualitative study, the dialogues and monologues in the textbook were examined to reveal the stereotyped concepts of gender and the deconstruction of the stereotyped concepts of gender. The data were observed under categories on deficit, dominance, and difference approach by Lakoff, supported by critical perspective of language and gender from Coates. The result of the study revealed that the textbook represents gendered language stereotypes in the use of lexical hedges and fillers, empty adjectives, intensifier along with male domination in the conversation. ‘Male firstness’ pattern of mentioning names, choice of topics, and focus of the conversation. However, the book has also included efforts to deconstruct the stereotypes through the deconstruction of conflict versus compromise and tag question usage. The results implies that future textbooks should include more deconstructions of gender stereotypes through language use, while teachers should use the present book with more critical approach to raise awareness about gender equity, especially through language use.